Elaboration of strength model of cylindrical joint with interference fit - Куприянов, Александр Владимирович; Ламнауэр, Наталия Юрьевна (Eastern-European Journal of Enterprise Technologies, 2015)
In the case of using the cylindrical joins with interference fit it is important to have a prediction of how much load it carries. For estimating the results of experiments the law of normal distribution is most often used. It is not suitable because of the physical reasons since it has no lower limit. A three-parameter probabilistic model of the strength of the cylindrical joins with interference fit is proposed. It allows calculating the allowable carries value on the results of the small number of experiments. The model contains finite lower bound strength. It is found evaluation of all three model parameters and it is given the method of their calculation for small sample. It is explained the practical application of the model. The model is tested on the strength results experiments of 11 shaft-hub joins with diameter 60 mm. It confirmed its efficiency and effectiveness. An example of the strength and failure rate curves of joins is constructed, that is match with experimental data. Model will be use in mechanical engineering for predicting strength of the cylindrical joins in a case of limited number of experiments.